Strategi Pemasaran Merica Dalam Meningkatkan Pendapatan Masyarakat Desa Larui Kecamatan Porehu Kabupaten Kolaka Utara - Ananda Fajarwati; Wa Ode Rayyani (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to describe and analyze the pepper marketing strategy implemented by the people of Larui Village, Porehu District, North Kolaka Regency in an effort to increase their income. Pepper is a leading commodity in the area and is the main source of income for the community. The results of the study showed that the marketing strategies carried out by the community varied, ranging from direct sales to the market, selling to middlemen, to through cooperatives or consignment systems. Supporting factors for marketing strategies include the cohesiveness of farmer groups and the availability of road access, while obstacles include lack of marketing knowledge, unstable prices, and limited market networks. A more active and organized marketing strategy has been shown to provide better income for farmers compared to traditional strategies that are passive and dependent on intermediaries.